Um Influence of inclusion of low doses of tannin blends in beef cattle dietary supplements on in vitro and in situ digestibility of nutrients in some feedstuffs - Adrielle Torres Mundim; Matheus Lima Corrêa Abreu; ‪Joanis Tilemahos Zervoudakis; Ronyatta Weich Teobaldo; Luciano da Silva Cabral; Mozart Alves Fonseca; Gabriela Fernandes dos Santos Teodoro; Victória Curvo Ormond; Nelcino Francisco Paula (Semina: Ciências Agrárias, 2023)
The objective of this study was to evaluate the effects of the daily supplementation with a low dosage of a blend of condensed and hydrolysable tannins on the in vitro and in situ digestibility of protein and fibrous feedstuffs. In situ ruminal incubation assays were conducted on seven protein and five roughage feedstuffs with and without tannin supplementation (1 g/kg DM intake). From these same cattle, rumen fluid was collected for in vitro incubations of the same feedstuffs. In vitro assays we evaluated the gas production (GP) up to 24 h and, sequentially, digestibility of dry matter (IVDMD), crude protein (IVCPD), fiber (IVNDFD), and ammonia nitrogen (NH3-N). For in situ assays, the disappearance curves were modeled and then the potentially degradable (), digestion rate (), and undegradable () fractions were estimated. Of all the variables studied, only IVCPD of soybean meal showed effect (P<0.05) with the addition of dose of tannins. The supplementation of tannin affected only  of the DM and CP of the cottonseed meal. The  of DM and CP increased with the supplementation of the tannin blend only for Marandu (dry season), soybean and cottonseed meal. Additionally, the  of the DM of corn silage was reduced. The  of CP was affected by the increase of tannin supplementation for soybean and cottonseed meal. Daily supplementation with a low dose of tannin blend for grazing cattle affects for grazing cattle affects the ruminal digestibility of some of the evaluated feedstuffs, which are soybean and cottonseed meal.